PHOSPHATE SOLUBILIZING BACTERIA IN COMBINATION WITH PRESSMUD IMPROVE GROWTH AND YIELD OF MASH BEAN - M. T. H. Niazi; Saif-ur-Rehman Kashif; H. N. Asghar; M. Saleem; M. Y. Khan; Z. A. Zahir (Journal of Animal and Plant Sciences, 2015)
Phosphorus (P) is an important macronutrient for growth of plants and is often provided to crops by the application of inorganic sources; 80 percent of that cannot be utilized by crops due to immobilization and precipitation. In such situation, phosphate solubilizing bacteria (PSB) may play a major role in improving P availability to plants by dissolving insoluble and fixed soil P. Moreover, phosphatase activity of these PSB could further enhance the P availability from organic sources, if supplemented with organic amendments. A pot experiment was conducted to evaluate the potential of PSB containing phosphatase activity with and without organic amendment (pressmud) for improving growth and yield of mash bean. Mash bean seeds were inoculated with 4 different well characterized PSB strains [PS-01 (Burkholderia sp.), PS-12 (Bacillus sp.), PS-32 (Pseudomonas sp.) and PS-41 (Flavobacterium sp.)]. The inoculated seeds were sown in potted soil amended with and without press-mud. Results showed that combined use of PSB strain (PS-01) and PrM caused significant increase in yield (38 and 69%), P content in root (1.3 and 3.3 fold) and in shoot (32 and 136%) of mash bean as compared to sole use of PS-01 and PrM, respectively. This approach could be very effective to enhance the phosphorous availability to plants, plant growth and yield.
Keywords: phosphorous; phosphatases; rhizobacteria